1974
DOI: 10.1149/1.2401784
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Active Chlorine and the pH on Consumption of Graphite Anode in Chlor-Alkali Cells

Abstract: Corrosion tests of graphite anodes in saturated normalNaCl solution at 40δC have been carried out at 100 A/dm2. The corrosion rate was a small function of the pH between 2 and 9, but affected by the active chlorine. Electrochemical formation of chlorate is a side reaction and is limited by slow diffusion of normalHClO and/or normalClO minus;. While chlorate does not affect degradation of graphite anode either electrochemically or chemically, the carbon surface oxide, which forms during electrochemical fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Corrosion of graphitic carbon in aqueous sodium chloride medium has been extensively studied in the literature. [60][61][62][63][64] According to Rabah et al, 60 during electrolysis of brine employing graphite electrodes, some carbon atoms are ionized followed by adsorption of chloride ions on certain active sites on the anode. The adsorbed chloride ions then react with partially ionized, positively charged carbon atoms to form C 4 OH 2 Cl, which is water-soluble and could decompose to carbon, carbon monoxide, carbon dioxide, chlorine, and water.…”
Section: A78mentioning
confidence: 99%
“…Corrosion of graphitic carbon in aqueous sodium chloride medium has been extensively studied in the literature. [60][61][62][63][64] According to Rabah et al, 60 during electrolysis of brine employing graphite electrodes, some carbon atoms are ionized followed by adsorption of chloride ions on certain active sites on the anode. The adsorbed chloride ions then react with partially ionized, positively charged carbon atoms to form C 4 OH 2 Cl, which is water-soluble and could decompose to carbon, carbon monoxide, carbon dioxide, chlorine, and water.…”
Section: A78mentioning
confidence: 99%
“…In concentrated chloride solutions the presence of sulphate ions in the solution strongly increased the graphite anodic corrosion, but it was not noticed in dilute solutions [23]. The corrosion of graphite composite has been investigated by Beck et al [24] in 1-18 M H 2 SO 4 and 1-12 M HClO 4 .…”
Section: Local Analysismentioning
confidence: 99%
“…The corrosion of carbon was studied by many authors [20][21][22][23][24][25][26][27][28]. Kinoshita and Bett [20,21] reported that the formation of a surface oxide and evolution of carbon dioxide (CO 2 ) occurred during the electrochemical oxidation of different carbons in H 3 PO 4 solution at temperatures up to 135 • C. A protective oxide (graphite oxide) and a surface oxide were found to form when the anodic current was imposed during the electrolysis of carbon electrodes in HCl [22].…”
Section: Introductionmentioning
confidence: 99%
“…During the electrolysis of a brine solution, carbon anode electrodes undergo oxidation, slow mechanical disintegration, and eventual failure [ 39 , 40 , 45 ]. This process occurs not only on the surface of the electrodes but also within their high-porosity structure.…”
Section: Methodsmentioning
confidence: 99%
“…Before use, the electrodes were rinsed with tap water and brushed with a nylon brush to remove loose carbon particles. The carbon gouging rods, shown in Fig 2, allow for chlorine production while gradually degrading due to oxidation [39][40][41]. Despite the undesirability of electrode disintegration, the use of low-cost carbon is preferred over other alternatives such as stainless steel, which rusts in the presence of chloride ions [42][43][44].…”
Section: Reactor Materials and Designsmentioning
confidence: 99%